1997
DOI: 10.1002/pc.10320
|View full text |Cite
|
Sign up to set email alerts
|

Resin flow in a pultrusion process

Abstract: A simple model for the resin flow in a pultrusion die based on the theory of lubrication has been developed. The velocity field in the pultrusion die has been calculated together with the pressure drop. A useful tool to evaluate the energy loss due to the viscosity dissipation along the die has been developed. Model results have been evaluated, by using chemorheological submodels, in terms of the contribution to the pulling force due to the viscous drag.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Continuous fiber composite materials have been widely used in the aerospace field, as well as in high-technology products [1][2][3][4][5][6][7][8][9][10]. Polymericcomposite materials offer many advantages compared to metals, mainly because they exhibit high strength and stiffness-to-weight ratio, excellent fatigue properties and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous fiber composite materials have been widely used in the aerospace field, as well as in high-technology products [1][2][3][4][5][6][7][8][9][10]. Polymericcomposite materials offer many advantages compared to metals, mainly because they exhibit high strength and stiffness-to-weight ratio, excellent fatigue properties and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…This technology offers the integration of high volume fraction of fibre impregnation and composite consolidation in the same process (Giordano and Nicolais, 1997). The ease of production, the cost effectiveness and high productivity of this process made pultrusion one of the interesting methods over others for the fabrication fibre composite products (Sharma et al, 1998a;1998b).…”
Section: Ajasmentioning
confidence: 99%
“…Sarrionandia et al (2002) suggested that a key for optimization of the pultrusion process is to master the polymerization reaction in the pultrusion die. Giordano and Nicolais (1997) reported that die temperature, polymerization reaction, rheological change of resin and resin viscosities are the variables affecting the behaviour of the pultruded composites. They also explained that polymerization reaction and rheological change of the resin strongly influenced the final properties and the quality of the pultruded products.…”
Section: Processing Parametersmentioning
confidence: 99%
“…This technology offered the advantages of continuous production, integration of fiber impregnation and composite consolidation in the same process. This simplicity, efficiency, and flexibility of this process make it one of the most interesting methods for the fabrication of continuous fiber composite products with constant cross‐section 7. Most of the literature published8–13 discussed its applications, some aspects of pultruded composites and the pultrusion process from the point view of monitoring the quality of incoming resins.…”
Section: Introductionmentioning
confidence: 99%